Existence of Positive Entire Solutions for Polyharmonic Equations and Systems (Journal of Partial Differential Equations, 2006)
In this paper, the existence results of positive entire solutions for supercritical polyharmonic equations and system are given.
Keywords: Positive entire solutions; polyharmonic equations; polyharmonic systems